Sowing time and crop geometry influences seed yield attributes and economics of Indian mustard (Brassica juncea) under irrigated conditions of Rajasthan (Journal of Oilseed Brassica, 2026)
An experiment was conducted on sandy loam soil to study the effect of time of sowing and crop geometry on yield attributes, seed yield and the economics of Indian mustard (Brassica juncea L) cultivar RH-749 under irrigated condition of Rajasthan. Results revealed that crop sown on October 24 recorded higher crop yield attributes including number of branches/plant, siliquae/plant, seeds/siliqua, seeds weight/plant, test weight, seed yield (2159 kg/ha) and economics with gross return (79898.64 Rs./ha), net return (54429.38 Rs./ha) and B:C ratio (3.14), respectively. The better plant growth and higher dry matter accumulation in yield components was also observed as compared to other date of sowing. Crop geometry of 45 x 30 cm recorded significantly increased branches/plant and seeds weight/plant (g) as compared to all other crop geometry while number of siliquae/plant and test weight increased significantly as compared to all other crop geometry except 45 x 15 cm crop geometry. Seed yield (2218 kg/ha), gross return (82085.61 Rs./ha), net return (56496.35Rs./ha) and B:C ratio (3.21) were increased significantly in crop geometry of 30 x 20 cm over to 30 x 10 cm and 45 x 30 cm crop geometry. Hence, the present study suggested to revise plant to plant spacing with similar line to lines spacing alongwith sowing in mid October could enhance the productivity of Indian mustard.